Cover Feature: Undesired Bulk Oxidation of LiMn2O4 Increases Overpotential of Electrocatalytic Water Oxidation in Lithium Hydroxide Electrolytes (ChemPhysChem 22/2019). Issue 22 (12th November 2019) - Baumung, Max; Kollenbach, Leon; Xi, Lifei; Risch, Marcel
Abstract : The Cover Feature illustrates the interplay between the activity for the oxygen evolution reaction and the battery charge state of LiMn2 O4 when used as a catalyst. The electrocatalyst remains in the discharged battery state at pH 14, whereas a charged battery state is observed as manganese oxidizes at lower pH values, wich leads to catalyst deactivation. More information can be found in the Article by M. Baumung et al. on page 2981 in Issue 22, 2019 (DOI: 10.1002/cphc.201900601 ).